Hubungan Antara Minat Belajar Bahasa Indonesia dengan Kemampuan Menulis Puisi Siswa Kelas X SMA Hang Tuah Makassar - Damayanti, Fina; Mayong, Mayong; Nurhusna, Nurhusna (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to: (1) Reveal the interest in learning Indonesian of class X students at Hang Tuah High School Makassar, (2) Reveal the ability to write poetry of class X students at Hang Tuah High School, Makassar. Data collection techniques through observation, questionnaires, performance tests, and documentation with a population of 120 people and a sample of 30 people. Data analysis using SPSS. 29. The results of this research show that the level of interest in learning Indonesian is classified as very weak with a score interpretation of 0% – 54% regarding feelings of happiness, interest, student attention, and student involvement. The ability to write poetry is classified in the very good category with an average score of 85.93 in terms of theme selection, diction, language style, imagery, and message. The results of the analysis and hypothesis based on the results of the Pearson's correlation test with a t-test significance value of 6.551 > 1.701 indicate that there is no very large or solid relationship between interest in learning Indonesian and the ability to write poetry in class X students at Hang Tuah High School, Makassar.